Metabolomics insights into diabetes nephropathy and protective effects of Radix Scutellariae on rats using ultra-high performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry. Issue 27 (15th March 2017) - Men, Lihui; Pi, Zifeng; Zhou, Yuan; Liu, Yuanyuan; Wei, Mengying; Song, Fengrui; Liu, Zhongying
Abstract : UHPLC-Q-TOF-MS based metabolomics combined with multivariate statistical analysis for evaluating protective effects of Radix Scutellariae on DN rats. Abstract : Diabetic nephropathy (DN) is the most prevalent microvascular complication in diabetes contributing to high mortality. Radix Scutellariae is one of the most commonly used traditional Chinese medicines (TCM) and has played an important role in treating DN. In this study, a urine metabolomics method based on ultra-high performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UHPLC-Q-TOF-MS) has been established to explore the metabolic variations in DN rats and investigate the therapeutic effect of Radix Scutellariae on DN in the different stages (6th week and 10th week). Multivariate analysis approaches were applied to differentiate the components between a Radix Scutellariae -treated group, a model group and a normal group. A series of urinary endogenous metabolites were screened for DN rats, suggesting metabolic dysfunction in pathways of tryptophan, phenylalanine, tyrosine, purine, pyrimidine, and energy metabolism. Treatment with Radix Scutellariae could reverse urinary metabolite abnormalities, and subsequently influenced the above disordered pathways, which were remarkably involved in inhibition of oxidative stress, inflammation and attenuation of several enzymes altered in DN. Our results thus provide an overall view of the progression of DN, and nephroprotective effects of Radix Scutellariae against DN.